Two novel heterozygous truncating variants in NR4A2 identified in patients with neurodevelopmental disorder and brief literature review - Song, Xiaozhen; Xu, Wuhen; Xiao, Man; Lu, Yanfen; Lan, Xiaoping; Tang, Xiaojun; Xu, Nanjie; Yu, Guangjun; Zhang, Hong; Wu, Shengnan (Frontiers in Neuroscience, 2022)
Although some studies have indicated the importance of NR4A2 in neurological disorders, more supporting evidence from independent research is needed to strengthen the association between this gene and disease. Here, we report two novel variants in NR4A2 and briefly review the clinical and genetic characteristics of reported patients. The variants were identified by whole-exome sequencing and Sanger sequencing and were confirmed de novo. A minigene assay was used to reveal the splicing variation responsible for the aberrant transcripts. A Western blot was performed to determine protein expression. Two truncating mutations in NR4A2 were identified in two Chinese families: a novel splicing variant (NM_006186.3: c.1541-2A>C) and a nonsense variant (NM_006186.3: c.915C>A). Both cases presented with developmental delay, language impairment, and attention deficit hyperactivity disorder. The c.1541-2A>C mutation caused aberrant splicing, resulting in the retention of intron 7, which led to the truncation of the protein—due to an early termination codon within intron 7—and decreased protein expression in vitro. The c.915C>A variant resulted in a truncated protein and an increase in expression in vitro. The identified variations were causative of the two patients’ neurological phenotypes. Our research further highlights the importance of NR4A2 as a disease-related gene in neurodevelopmental disorders.